Distinct expression patterns of mitochondrially localized YFP in neuronal subsets in the retina of three transgenic mouse lines - Fuerst Peter G; Burgess Robert W (BMC Research Notes, 2010)
Abstract Background Transgenic labels that allow the visualization of specific populations of neurons have proven to be powerful tools for research. Further developing such resources to label additional cell types and specific organelles within these cell will provide additional experimental opportunities. Findings The retinal expression profile of a mitochondria-localized yellow fluorescent protein (YFP) in each of three transgenic mouse lines was determined. Each line, Mito-R, Mito-Y and Mito-Z, expresses YFP in distinct and reproducible populations of retinal neurons. In the Mito-R line, YFP is expressed in most or all retinal ganglion cells (RGCs) and photoreceptors making this line useful for studying axonal transport in diseases such as glaucoma and photoreceptor degeneration related to transport of mitochondria into the inner segments. In the Mito-Y line, YFP is expressed in many cell types in the dorsal retina and in a rough mosaic population of RGCs in the rest of the retina, making this line useful for study of how retinal mosaics are organized. In the Mito-Z line, YFP is expressed in a subset of RGCs, amacrine cells, bipolar cells and photoreceptors. The Mito-Z line is inserted on the X-Chromosome, resulting in X-inactivation mosaicism in female mice carrying a single copy of the transgene. In the female hemizygous retina, expression is present in distinct clonal columns, making this transgenic line useful for analysis of clonal proliferation and lateral migration of retinal neurons. Conclusion The retinal expression profiles of three transgenic mouse lines that express a mitochondrially localized YFP were characterized in this study. These lines will allow researchers to isolate and identify cell types within the retina and to study retinal mitochondrial trafficking and disease.